2007
DOI: 10.1303/aez.2007.629
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation in the amounts of pheromone components in the male bean bug, Riptortus pedestris (Heteroptera: Alydidae) and its attractiveness to the same species

Abstract: The individual variation of R. pedestris males and females in their attractiveness to the same species and the amounts of five pheromone components were examined in field experiments and GC-MS analysis, respectively. The number of adults attracted by a single male varied greatly among the individuals tested. The number of adults attracted was 0.92Ϯ0.12 (meanϮSE/day). Of 64 males examined individually, four attracted three or more adults per day, while 12 males attracted only 0.5 adults or fewer per day and 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…Mizutani et al (2007) showed that there was individual variation in R. pedestris males in their attractiveness to the same species, and in the amount of pheromone produced. Endo et al (2007) revealed that adult age and reproductive diapause affect the production of pheromone components in P. hybneri males.…”
Section: Effects Of Temperaturementioning
confidence: 99%
“…Mizutani et al (2007) showed that there was individual variation in R. pedestris males in their attractiveness to the same species, and in the amount of pheromone produced. Endo et al (2007) revealed that adult age and reproductive diapause affect the production of pheromone components in P. hybneri males.…”
Section: Effects Of Temperaturementioning
confidence: 99%
“…Males attracting conspecific adults and nymphs contained 14:iBu (Mizutani et al, 2007). In the present study, males used as attractants were determined to contain 14:iBu by GC-MS analysis; however, most of the males attracted to bait males during non-diapause and all males attracted to bait males during diapause did not contain 14:iBu, which is an essential component of the R. pedestris pheromone.…”
Section: Discussionmentioning
confidence: 58%
“…In males used as attractants in field experiments, males having well-developed fat-bodies showed a tendency to have more 14:iBu than those with undeveloped fat-bodies (Mizutani et al, 2007). These results indicate that the production of pheromone components including 14:iBu and the nutritional condition of males are closely related in R. pedestris.…”
mentioning
confidence: 68%
See 2 more Smart Citations